Critical by Design? Genealogies, Practices, Positions - Mareis, Claudia; Greiner-Petter, Moritz; Renner, Michael (Design, 2022)
In its constructive and speculative nature, design has the critical potential to reshape prevalent socio-material realities. At the same time, design is inevitably normative, if not often violent, as it stabilises the past, normalises the present, and precludes just and sustainable futures. The contributions rethink concepts of critique that influence the field of design, question inherent blind spots of the discipline, and expand understandings of what critical design practices could be. With contributions from design theory, practice and education, art theory, philosophy, and informatics, »Critical by Design?« aims to question and unpack the ambivalent tensions between design and critique.